Ultra‐Sharp Nanowire Arrays Natively Permeate, Record, and Stimulate Intracellular Activity in Neuronal and Cardiac Networks. (6th November 2021) - Liu, Ren; Lee, Jihwan; Tchoe, Youngbin; Pre, Deborah; Bourhis, Andrew M.; D'Antonio‐Chronowska, Agnieszka; Robin, Gaelle; Lee, Sang Heon; Ro, Yun Goo; Vatsyayan, Ritwik; Tonsfeldt, Karen J.; Hossain, Lorraine A.; et al.
Abstract: Intracellular access with high spatiotemporal resolution can enhance the understanding of how neurons or cardiomyocytes regulate and orchestrate network activity and how this activity can be affected with pharmacology or other interventional modalities. Nanoscale devices often employ electroporation to transiently permeate the cell membrane and record intracellular potentials, which tend to decrease rapidly with time. Here, one reports innovative scalable, vertical, ultrasharp nanowire arrays that are individually addressable to enable long‐term, native recordings of intracellular potentials. One reports electrophysiological recordings that are indicative of intracellular access from 3D tissue‐like networks of neurons and cardiomyocytes across recording days and that do not decrease to extracellular amplitudes for the duration of the recording of several minutes. The findings are validated with cross‐sectional microscopy, pharmacology, and electrical interventions. The experiments and simulations demonstrate that the individual electrical addressability of nanowires is necessary for high‐fidelity intracellular electrophysiological recordings. This study advances the understanding of and control over high‐quality multichannel intracellular recordings and paves the way toward predictive, high‐throughput, and low‐cost electrophysiological drug screening platforms. Abstract : Innovative scalable, vertical, ultrasharp nanowire arrays are reported that are individually addressable to enable long‐term, native recordings of intracellular potentials. Stable amplitudes of intracellular potentials from 3D tissue‐like networks of neurons and cardiomyocytes are obtained. Individual electrical addressability is necessary for high‐fidelity intracellular electrophysiological recordings. This study paves the way toward predictive, high‐throughput, and low‐cost electrophysiological drug screening platforms.